Experimental determination of the epithermal neutron sensitivity of a new ionization chamber. (September 2016) - Sato, H.; Nakajima, E.; Gotanda, R.; Endo, S.; Suda, M.; Hamano, T.; Hoshi, M.
Abstract : Introduction: The resulting improvement in the accuracy of the determination of the dose from gamma rays and epithermal and fast neutrons is important in view of the required accuracy for dosimetry in accelerator based neuron sources. Purpose: A new ionization chamber detector is being developed for the epithermal neutron dosimetry at accelerator based neuron sources. To obtain a high accuracy in the dosimetry of an epithermal neutron beam used for boron–neutron capture therapy (BNCT), the neutron sensitivity of dosimeters applied to determine the various dose components in polyethylene phantom has been investigated. Materials and methods: Well-stabilized neutron filed of Neutron exposure Accelerator System for Biological Effect Experiments (NASBEE) in National Institute of Radiological Sciences (NIRS) was used in this study. The epithermal neutron sensitivity LBO ionization chamber, tissue equivalent ionization chamber, and optically stimulated luminescence (OSL) dosimeters has been experimentally determined in a neutron beam fields. Results: The epithermal neutron values much higher than theoretically expected were obtained and a variation up to a factor of 1.8 was found between values for the epithermal neutron sensitivity. The ratio of a gamma dose and a thermal neutron dose was 23% in a depth of 30 mm. Conclusion: The new epithermal ionization chamber response characteristic was evaluated at the accelerator based neutron sources field. Disclosure: This work was supported byJSPS Kakenhi Grant Number15K00544 .